Membelajarkan Numerasi Menggunakan Erupsi Gunung Rinjani bagi Guru Gugus Suela - Ni Made Intan Kertiyani; Nourma Pramestie Wulandari1; Gilang Primajati; Nyoman Sridana Kertiyani; Nurul Hikmah; Septyani Nanda Dewi Kertiyani (Rengganis Jurnal Pengabdian Masyarakat, 2026)
Numeracy has become one of the Indonesian government’s priority programs to improve the quality of the national education report. In 2024, the education report of SDN 2 Suela indicated that student numeracy skills required significant improvement. Interviews with teachers at the school revealed that they face challenges in implementing numeracy within the local context and still lack a deep understanding of numeracy concepts. To address this issue, a workshop was conducted to strengthen teachers’ understanding and implementation of numeracy through conceptual reinforcement, lesson planning, and classroom practices. The methods included: (a) introducing the cultural context of the Sasak community and Rinjani Geopark as potential resources for numeracy learning, (b) training teachers on strengthening numeracy concepts and classroom implementation, and (c) utilizing a numeracy module developed by the community service team to be implemented and adapted in classroom learning. The participants’ responses were highly positive, as evidenced by their commitment to continue using the module while making necessary preparations to ensure its effective application.